Effect of Free Cash Flow and Stock Trading Volume Moderated Diversification of Business Toward Stock Yield - Situngkir, Tiar Lina (SENTRALISASI, 2025)
The research intents to investigate the effect of free cash flow and stock trading volume on stock returns with business diversification as a moderating variable. The problem raised is how the interaction between free cash flow, stock trading volume, and business diversification affects stock returns. The research sample consisted of 11 pharmaceutical firms existed on the Indonesian Securities Exchange during the period 2018-2022, but only 8 firms were validated so that the sample used was 40 confirmed data. The data analysis method used is multiple linear regression and moderation regression analysis (MRA). The results demonstrated that free cash flow has no substantial impact on stock yield, while stock trading volume has a substantial impact directly. However, it was found that business diversification does not restrain the free cash flow and stock trading volume effect on stock yield. The focus conclusion of this research is only stock trading volume affects stock yield. Meanwhile, free cash flow and stock trading volume do not interact with business diversification on stock yield. The implication is that investors and various interested parties need to consider the volume of stock trading in determining investment decisions, in order to obtain maximum yield.